2013
DOI: 10.3126/jnps.v33i1.7404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status: A Case of Tribal Children in Assam, Northeast India

Abstract: Introduction: Thinness is a major underlying problem among children and adolescents in the developing countries including India. The present study was carried out to determine the prevalence of nutritional status among the Sonowal Kachari children aged 6-18 years of Dibrugarh district of Assam, Northeast India. Materials and Methods: The cross-sectional data on height and weight measurements were collected among 1343 (670 boys, 673 girls) children belonging to Sonowal Kachari tribal ethnic group using multi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…However, in rural areas, the male child had higher rates of underweight and stunting as compared to the female child. This is similar to other studies as reported by Singh and Mondal (2013), and Basu et. al (2014).…”
supporting
confidence: 83%
“…However, in rural areas, the male child had higher rates of underweight and stunting as compared to the female child. This is similar to other studies as reported by Singh and Mondal (2013), and Basu et. al (2014).…”
supporting
confidence: 83%
“…Moreover, the newly proposed references 16 was derived using the mul centre data of the United States, Great Britain, Hong Kong and the Netherlands including data from Brazil (developing country). Several studies have already assessed the prevalence of thinness u lizing this newly proposed reference 16 among Indian children and adolescents 13,29,30,31,35,36,37,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14] In the present study, the boys were found to be a more suff erer than the girl counterparts (p>0.05). It has also been observed that boys were more suff erer than girls in thinness among tribal and non-tribal children and adolescents residing in rural and sub-urban regions in India 7,13,14,31,35,37,38,39 . The comparison with the present study showed that the prevalence of overall thinness was found lower than the children and adolescents belonging to Bengalee 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations